Inspædia report: an inspired research itinerary - Maldonado, Paulo (2018)
This article summarizes the essentials of the design research path that led to the collaborative and interactive intelligence platform Inspædia. Firstly, it discusses the concepts and contexts that favor innovation to understand the importance of entrepreneurship, exploring successful business models and identifying trends and patterns of excellence; some inspirational riffs to inspire other organizational contexts are selected; there is a review of authors who have emphasized the importance of designing and developing user-oriented business models – or rather, producers that are at the same time consumers (prosumers), connected by collaborative intelligence networks; creative and collaborative cognition in design is explored by presenting some strategies to activate divergent thinking, and the conceptual model of Inspædia is described. Secondly, the article contextualizes and describes the research journey to redefine and simplify the conceptual model to bring the online platform to life. Finally, the results obtained and the feedback given by some inspædiers are presented.